The legal status of the arbitration manager in bankruptcy case in Ukraine - Butyrska, Iryna (My University, 2014)
The existing views on the nature o f the legal status o f the arbitration manager in Ukraine are analyzed. The characteristic of the general, special and individual legal status of the arbitration manager in bankruptcy case is made. It is established that the trustee in bankruptcy is a specific participant of the bankruptcy case that has a specific public law status, due to the peculiarities of bankruptcy cases.
Правовий статус арбітражного керуючого у справі про банкрутство в Україні
Keywords: банкрутство; арбітражний керуючий; bankruptcy; arbitration manager; insolvency; bankruptcy case; неплатоспроможність; справа про банкрутство